Becoming a business: an environmental, transitional and organisational analysis of Bradford and Queen's Park Football Clubs before 1914. (18th May 2020) - Dewhirst, John; Vamplew, Wray
ABSTRACT: This study offers a tripartite approach to the analysis of the transition of two football clubs, one in England and the other in Scotland, from their beginnings as recreational football clubs to them becoming significant sports businesses by 1914. First, an environmental review assesses external themes and the economic factors that shaped change; second a transformational review looks at the dynamics of becoming a business; and, finally, an organizational review examines the internal characteristics of the clubs as businesses.